Pengaruh Kualitas Pelayanan Administrasi Kepegawaian dan Kepuasan Kerja Terhadap Kinerja - Suharno Suharno; Muhammad Syarif Hidayatullah Elmas; Seger Priantono (Fakultas Ekonomi Universitas Panca Marga, 2020)
This study to determine effect quality of personnel administration services on employee performance in the Treasury and Regional Cash Fields of Probolinggo City, and determine effect of employee job satisfaction on employee performance in the Treasury and Regional Cash Fields of Probolinggo City. This type of research is causal research . The method of data collection by questionnaire, a sample of 47 employees of the Treasury and Regional Cash of the City of Probolinggo with a sampling method that is saturated sample. Data analysis method in the form of multiple linear regression analysis. The results that employee job satisfaction has a significant influence on employee performance variables in the Treasury and Regional Cash Fields of Probolinggo City.